Harnessing policy to promote inclusive medical product evidence: development of a reference standard and structured audit of clinical trial diversity policies - Joseph S Ross; Jennifer Miller; Cary Gross; Reshma Ramachandran; William Pelletiers; Sakinah Suttiratana; Michael Ofosu Mensah; Jason Schwartz (BMJ Medicine)
Objective To develop a reference standard based on US Food and Drug Administration and stakeholder guidance for pharmaceutical companies' policies on diversity in clinical trials and to assess these policies.Design Development of a reference standard and structured audit for clinical trial diversity policies.Setting 50 pharmaceutical companies selected from the top 500 by their market capitalizations in 2021 (the 25 largest companies and 25 non-large companies, randomly selected from the remaining 475 companies).Population Data from pharmaceutical company websites and annual reports. Policy guidance from the Pharmaceutical Research and Manufacturers of America, International Federation of Pharmaceutical Manufacturers and Associations, Biotechnology Industry Organization, International Committee of Medical Journal Editors, the US Food and Drug Administration, European Medicines Agency, and World Health Organization, up to 15 May 2023.Main outcome measures Multicomponent measure based on distinct themes derived from FDA and stakeholder guidance.Results Reviewing FDA and stakeholder guidance identified 14 distinct themes recommended for improving diversity in clinical trials, which were built into a reference standard: (1) enrollment targets that reflect the prevalence of targeted conditions in populations, (2) broad eligibility criteria for trials, (3) diversity in the workforce, (4) identification and remedy of barriers to trial recruitment and retention, (5) incorporation of patient input into trial design, (6) health literacy, (7) multidimensional approaches to diversity, (8) sites with diverse providers and patient populations, (9) data collection after product approval, (10) diverse enrollment in every country where trials are conducted, (11) diverse enrollment should be a focus for all phases of clinical trials, not just later stage or pivotal trials, (12) varied trial design, (13) expanded access, and (14) public reporting of the personal characteristics of participants in trials. Applying this reference standard, 48% (24/50) of companies had no public policy on diversity in clinical trials; among those with policies, content varied widely. Large companies were more likely to have a public policy than non-large companies (21/25, 84% v 5/25, 20%, P<0.001). Large companies most frequently committed to using epidemiological based trial enrollment targets representing the prevalence of indicated conditions in various populations (n=15, 71%), dealing with barriers to trial recruitment (n=15, 71%), and improving patient awareness of trial opportunities (n=14, 67%). The location of the company was not associated with having a public diversity policy (P=0.17). The average company policy had five of the 14 commitments (36%, range 0-8) recommended in FDA and stakeholder guidance.Conclusions The findings of the study showed that many pharmaceutical companies did not have public policies on diversity in clinical trials, although policies were more common in large than non-large companies. Policies that were publicly available varied widely and lacked important commitments recommended by stakeholder guidance. The results of the study suggest that corporate policies can be better leveraged to promote representation and fair inclusion in research, and implementation of FDA and stakeholder guidance.